PENGARUH SANKSI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI KOTA BANJARMASIN - Soedjatmiko -; Sri Mulyani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research aims to examine the effect of tax sanctions and awareness of taxpayers on taxpayer compliance in paying land and building tax (PBB) in the city of Banjarmasin. The research population consisted of Land and Building Tax Obligations (PBB) in Banjarmasin City in 2017 data obtained from the Banjarmasin City Revenue Service (Dispenda) stated that it was obtained for 1 (one) year as many as 190,014 people. The research sample used in this study is Random Sampling. Sampling for this study uses the Slovin formula totaling 100 people. The results of this study indicate that partially the tax sanction variable affects taxpayer compliance, while the taxpayer's awareness variable does not affect taxpayer compliance. Simultaneously shows that the variables of tax sanctions and awareness of taxpayers affect taxpayer compliance. The R square determinant test results show the effect of tax sanctions and taxpayer awareness on taxpayer compliance by 76% which has a large influence while the remaining 24% is influenced by other variables not included in this study. The conclusions of this study are that only independent tax sanction variables have a significant effect on the dependent variable of taxpayer compliance. While simultaneously independent variables of tax sanctions and awareness of taxpayers affect the dependent variable taxpayer compliance is due to tax sanctions and awareness of taxpayers is important information used in increasing taxpayers in paying land and building tax (PBB).